Topological photonic crystal nanocavity laser. Issue 1 (December 2018) - Ota, Yasutomo; Katsumi, Ryota; Watanabe, Katsuyuki; Iwamoto, Satoshi; Arakawa, Yasuhiko
Abstract Topological edge states exist at the interfaces between two topologically distinct materials. The presence and number of such modes are deterministically predicted from the bulk band topologies, known as the bulk-edge correspondence. This principle is highly useful for predictably controlling optical modes in resonators made of photonic crystals (PhCs), leading to the recent demonstrations of microscale topological lasers. Meanwhile, zero-dimensional topological trapped states in the nanoscale remained unexplored, despite its importance for enhancing light–matter interactions and for wide applications including single-mode nanolasers. Here, we report a topological PhC nanocavity with a near-diffraction-limited mode volume and its application to single-mode lasing. The topological origin of the nanocavity, formed at the interface between two topologically distinct PhCs, guarantees the existence of only one mode within its photonic bandgap. The observed lasing accompanies a high spontaneous emission coupling factor stemming from the nanoscale confinement. These results encompass a way to greatly downscale topological photonics. For most lasing and photonic applications, it is essential to control the number of lasing modes that are present. In this work, an interface between two topologically distinct photonic crystals is used to ensure single-mode lasing with enhanced light-matter interactions due to a near-diffraction-limited mode volume.